Lingual frenectomy with ND:YAG laser. Case report - Pares Perfetti, Adriana (2023)
Ankyloglossia is considered a congenital patology, whose treatment indicated is a frenectomy, this surgical technique consists in remove the tissue that joins the tongue with the floor mouth.This technique allows the patient a considerable improvement to limitations caused by this anomalysuch as difficulties in suction, pronunciation, chewing and difficulty in touching the lower lip with the tip of the tongue. Currently the use of laser technology and its benefits in modern dentistry, allows the realization of surgical procedures free of bleeding, with very little pain and inflammation of the tissues and with a recovery time much lower than necessary with conventional techniques. The present clinical case, show a 12-year-old patient with severe ankyloglossia, lingual frenectomy was indicated. A contact Nd: YAG laser was used, achieving a quirurgical intervention with little pain, free bleeding and without suture.